2019
DOI: 10.4236/fns.2019.108066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Monascus</i> Fermentation on Aroma Patterns of Semi-Dried Grass Carp

Abstract: The aim of the present study is to investigate the effects of Monascus fermentation on the aroma pattern of semi-dried grass carp. Semi-dried fish was fermented using Monascus purpureus GDMCC3.439. The volatile flavor substances present in fresh fish, semi-dry fish and Monascus fermented semi-dried fish were compared by simultaneous distillation and extraction combined with gas chromatograph-mass spectrometer (GC-MS). The results showed that alcohols, aldehydes and ketones were the main components of the flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Fukami et al (2004) inoculated flattened carp sauce with staphylococcus at 32 °C for 24 days, and found that the fishy odour and sweaty odour were significantly reduced in the product. Monascus fermentation of semi-dried fish could not only effectively improve the fishy smell of fresh fish but also recover the defect of the pickled flavour of semi-dried fish (Wu et al, 2019).…”
Section: Chemical Deodorisation Technologymentioning
confidence: 99%
“…Fukami et al (2004) inoculated flattened carp sauce with staphylococcus at 32 °C for 24 days, and found that the fishy odour and sweaty odour were significantly reduced in the product. Monascus fermentation of semi-dried fish could not only effectively improve the fishy smell of fresh fish but also recover the defect of the pickled flavour of semi-dried fish (Wu et al, 2019).…”
Section: Chemical Deodorisation Technologymentioning
confidence: 99%
“…The PCA results of skin sample were consist with those of muscle samples (Figure 3b). Note: The threshold and odor attributes were found from previous study [2,[19][20][21][22]. "-" represents not detected; "*" represents significant figures.…”
Section: Flavor Characteristics Analysismentioning
confidence: 99%
“… Note: The threshold and odor attributes were found from previous study [ 2 , 19 , 20 , 21 , 22 ]. “–” represents not detected; “*” represents significant figures.…”
Section: Figurementioning
confidence: 99%
“…Flavor formation occurs through a series of biochemical and physical changes and depends on microorganism fermentation and/or endogenous enzyme action [1][2][3]. During fermentation, a number of aromatic substances, such as free amino acids (AAs), aldehydes, alcohols, acids, heterocyclic compounds and nucleotides, can be formed which impart a unique flavor to the food [4][5][6][7]. Due to lower water activity (aw) and higher salinity, fermented dry/semi-dry products can be stored for a long time with minimal microbial reproduction.…”
Section: Introductionmentioning
confidence: 99%